Research Evaluation: Mapping the Field Structure (Avaliação: Revista da Avaliação da Educação Superior, 2020)
The Research Evaluation topic has been the object of intense study both for its importance for multiple purposes, and as for theoretical development model system on continuous increase of quality of research performance and societal and innovation impact. The objective of this exploratory study is to capture the intellectual structure of Research Evaluation. Using networks citations we capture the latent building blocks and drivers of this theme. Data visualization and visual analytics were helpful to make an exploration of literature background; by observing citation networks and its clusters we identify key papers (seminal and highest papers) that support different areas of Research Evaluation. The main result is the Citation map with six clusters, where each cluster gives us a quick overview of those interlinked territories that provide an understanding of those different knowledge areas. This is a clear picture of this topic, useful for academic scholars, novice researchers and the practical stakeholders, interest on research evaluation policy or on research evaluation implementation and its management implications. The evolution of Research Evaluation can be divided into 3 stages: 1- traditional peer review; 2 - actual bibliometric analytic focus and 3 - emerging scientific merit of research with quali and quantitative mix approach at project and networks levels. This study is the starting point for a deep literature review on “research evaluation”.